Prognostic significance of malignant pleural effusions in patients with advanced luminal B breast cancer - You-ming Han; Yan-Dong; Hai-long Wang; Xiang-Min Li; Xiao- Zhang; Xin-Yu Wei; Feng-Wen Qian; Zhi-Gang Li (BMC, 2024)
Abstract Background Though the survival of breast cancer (BC) patients with malignant pleural effusion (MPE) has been studied, this has not been specifically studied in the luminal B subtype. Therefore, this study investigated the characteristics and survival of luminal B-BC patients presenting with MPE. Methods We retrospectively analyzed 141 patients diagnosed with postoperative advanced Luminal B breast cancer, including 54 cases with MPE and 87 cases without MPE at the Tianjin Cancer Hospital from January 2012 to January 2015. We assessed the clinical characteristics between the groups. Results The mean age of all patients was 47 years, with no significant difference between the two groups. Altogether, 29 (33%), 24 (28%), 28 (32%), 45 (52%), and 10 (11%) patients had lung, liver, bone, lymph node, and chest wall metastases, respectively. In addition. The difference in overall survival between the two groups was not significant (P>0.05). However, cox regression analysis showed that only the tumor clinical stage at initial diagnosis was related to short overall survival. Further, we conducted a subgroup analysis and found that the higher the clinical stage at initial diagnosis in age < 50 years patients, the shorter the overall survival, while age > 50 years patients was not. (P < 0.05). Conclusions There was no difference in the overall survival between luminal B-BC patients with MPE and those without. Clinical stages at initial diagnosis were an independent prognostic factor for age < 50 years luminal B BC with MPE overall survival. Our results may help clinicians make positive decisions regarding personalized treatment of luminal B-BC with MPE.